Final Report on Contract N00014-84-K-0523 (California University, Santa Barbara) - Macdonald, Ken C.; Miller, Stephen P. (1988)
The long range scientific objectives of this contract is to achieve an understanding of crustal generation processes in the South Atlantic, approached with a combined analysis of Sea Beam bathymetric data and sea surface magnetic field data. We are particularly interested in small offset features on the spreading axis, which have a surprisingly large role in altering the normal seafloor fabric and magnetic signature. Keywords: South Atlantic Ocean, Oceanic crust, Seafloor spreading, Marine geology, Ocean ridges, Geomagnetism, Geologic faults.